(untitled) (Communications in Computational Physics, 2008)
The finite element method is a promising method for electronic structure calculations. In this paper, a new parallel mesh refinement method for electronic structure calculations is presented. Some properties of the method are investigated to make it more efficient and more convenient for implementation. Several practical issues such as distributed memory parallel computation, less tetrahedra prototypes, and the assignment of the mesh elements carried out independently in each sub-domain will be discussed. The numerical experiments on the periodic system, cluster and nano-tube are presented to demonstrate the effectiveness of the proposed method.